2011
DOI: 10.1016/j.molimm.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun and c-Fos regulate the complement factor H promoter in murine astrocytes

Abstract: The complement system is a critical component of innate immunity that requires regulation to avoid inappropriate activation. This regulation is provided by many proteins, including complement factor H (CFH), a critical regulator of the alternative pathway of complement activation. Given its regulatory function, mutations in CFH have been implicated in diseases such as age-related macular degeneration and membranoproliferative glomerulonephritis, and central nervous system diseases such as Alzheimer’s disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…As the most highly activated target of JNK, activated c-Jun has been reported to directly trans-activate many key genes involved in the inflammation process (17,52,53). Here we demonstrate that alox5 is a direct target of c-Jun and that it could be transcriptionally up-regulated by phosphorylated c-Jun.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As the most highly activated target of JNK, activated c-Jun has been reported to directly trans-activate many key genes involved in the inflammation process (17,52,53). Here we demonstrate that alox5 is a direct target of c-Jun and that it could be transcriptionally up-regulated by phosphorylated c-Jun.…”
Section: Discussionmentioning
confidence: 51%
“…5, E and F). c-Jun regulates the transcription of genes widely involved in cell migration, wound healing, and inflammation, and its activity is regulated by JNK (52)(53)(54). Decreased c-Jun-targeted gene transcription might be responsible for blocking leukocyte migration by Cnr2 activation.…”
Section: Inhibition Of Leukocyte Migration By Cnr2mentioning
confidence: 99%
“…Our study also found that although Cd activates multiple pathways in HRGECs, only the JNK pathway inhibitor eliminated the Cd-induced increase of CFH gene expression and CFH secretion, suggesting that the JNK/AP-1 pathway plays a key role in regulating the transcription of the CFH gene. In murine astrocytes, Fraczek et al (48) identified a 241-bp region at 2416 bp to 2175 bp on the mouse Cfh gene promoter that showed transcriptional activity with possible binding interactions with c-Jun and c-Fos. In the current study, we did not find AP-1 binding in the corresponding region on human CFH promoter in HRGECs but identified an AP-1 binding site at 21635 of the human CFH promoter, which mediates c-Jun-and c-Fosregulated CFH gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that systemically administered AMBP-1 can enter the brain after ischemic stroke (Chaung et al , 2011 ). Local AMBP-1 expression in the brain has also been shown in cerebral endothelial cells (Vastag et al , 1998 ), neurons (Thomas et al , 2000 ), and astrocytes (Fraczek et al , 2011 ). AMBP-1 regulates the complement cascade by binding to C3b and preventing the formation of the alternative complement pathway C3 convertase, C3bBb (Whaley and Ruddy , 1976 ).…”
Section: Ambp-1 and Complement Expression In The Brainmentioning
confidence: 98%